Sacred skin : the legend of St. Bartholomew in Spanish art and literature - Beresford, Andrew M. (Medieval and early modern Iberian world, 2020)
"Sacred Skin offers the first systematic evaluation of the dissemination and development of the cult of St. Bartholomew in Spain. Exploring the paradoxes of hagiographic representation and their ambivalent effect on the observer, the book focuses on literary and visual testimonies produced from the emergence of a distinctive vernacular voice through to the formalization of Bartholomew's saintly identity and his transformation into a key expression of Iberian consciousness. Drawing on and extending advances in cultural criticism, particularly theories of selfhood and the complex ontology of the human body, its five chapters probe the evolution of hagiographic conventions, demonstrating how flaying poses a unique challenge to our understanding of the nature and meaning of identity"--